Composition‐Conditioning Agent for Doped Spiro‐OMeTAD to Realize Highly Efficient and Stable Perovskite Solar Cells. Issue 44 (23rd September 2022) - Yang, Heyi; Shen, Yunxiu; Zhang, Rui; Wu, Yeyong; Chen, Weijie; Yang, Fu; Cheng, Qinrong; Chen, Haiyang; Ou, Xuemei; Yang, Haidi; Gao, Feng; Li, Yaowen; et al.
Abstract: The doped Spiro‐OMeTAD hole transport layer (HTL) formed using the lithium bis(trifluoromethane) sulfonimide salt and 4‐tert‐butylpyridine with phenethylammonium iodide surface treatment on a perovskite film has continuously dominated the record power conversion efficiencies (PCEs) of perovskite solar cells (pero‐SCs). However, unstable HTL compositions and iodide salts can cause severe device degradation. In this study, an HTL composition‐conditioning agent (CCA), Spiro‐BD‐2OEG, is designed, which contains a Spiro‐OMeTAD‐like backbone, functional pyridine units, and oligo (ethylene glycol) chains. This finely designed CCA presents good miscibility with Spiro‐OMeTAD and its dopants and acts as a conditioning agent through weak bond interactions. As a result, the CCA‐regulated HTL shows a pinhole‐free and smooth morphology with enhanced Spiro‐OMeTAD ordering and improves dopant stability. In addition, the gradient‐distributed CCA in the HTL can narrow the energy level offset with the valence band of the perovskite. The resultant pero‐SCs exhibit an excellent PCE of 24.19% without any interface treatment and weak size dependence. A remarkable PCE of 22.63% is obtained even for a 1.004‐cm 2 device. Importantly, the strategy shows good universality and significantly promotes the long‐term stability of the pero‐SCs based on the classical doped Spiro‐OMeTAD. Abstract : The Spiro‐BD‐2OEG with composition‐conditioning agent functionality is designed to improve the composition stability in the doped‐Spiro‐OMeTAD hole transport layer (HTL). By employing this strategy, the HTL shows a pinhole‐free and smooth morphology with an enhanced Spiro‐OMeTAD ordering. Finally, the resultant perovskite solar cells show an excellent power conversion efficiency of 24.19% and improved thermal, moisture, and operational stabilities.